Contrasting aerosol growth potential in the northern and central-southern regions of the North China Plain: Implications for combating regional pollution. (15th December 2021) - Wang, Yuying; Wang, Jingling; Li, Zhanqing; Jin, Xiaoai; Sun, Yele; Cribb, Maureen; Ren, Rongmin; Lv, Min; Wang, Qiuyan; Gao, Ying; Hu, Rong; Shang, Yi; et al.
Abstract: Aerosol growth potentials were investigated based on measurements of aerosol properties from three field campaigns carried out at sites in urban Beijing (BJ) and suburban Xingtai (XT) located in the North China Plain (NCP). BJ and XT were located in a northern megalopolis area and a central-southern industrial area, respectively, in the NCP. Results suggest new particle formation (NPF) events occurred more frequently, and the particle growth potential was greater in the central-southern NCP region than in the northern NCP region in summer. It is found that differences in primary emissions and meteorological conditions can cause regional and seasonal variations in aerosol growth potential in the NCP. Photochemical reactions were more important for particle growth in summer, while nocturnal aqueous chemical reactions were more important in winter. The large nocturnal particle growth rate (7.5 nm h −1 ) was the reason inducing the severe aerosol pollution in winter BJ. Further analyses of submicron aerosol chemical species indicate more sulfate in submicron aerosols at XT, suggesting that the growth of new particles in the central-southern NCP in summer may be mainly dominated by the secondary formation of inorganics. Diurnal variations in aerosol chemical species during the three field campaigns suggest that the downward vertical mixing of nitrate over the nocturnal boundary layer played an important role in aerosol growth in the morning in summer. Moreover, the enhanced anthropogenic emissions during the late-day rush hours can cause clear increases in nitrate and organics. Our results highlight the distinct aerosol growth potentials in the northern and central-southern areas of NCP, implying that different emission control measures are needed in two regions to further improve air quality in the future. Highlights: ● Diverse aerosol growth potentials were found in different regions of the North China Plain. ● Different particle growth mechanisms in winter and summer were reported. ● Distinct emission control measures are needed in different regions of the North China Plain to further improve air quality in the future.